e-Readiness among learners in Malaysia: An insight into fresh school leavers - Yoke, Lee; Chooi, Chea Chiam; Nyuk, Ling Lee (2010)
This paper aims to study the level of e-readiness among school leavers studying full-time. The higher education in Malaysian is facing a changing the delivering trend due to the effects of globalization, and the speed of change in the growth of communication. A book by Scott The Globalization of Higher Education has highlighted the radical processes of globalisation as implicating higher education as the creator, interpreter and sufferer of such trends (Scott, 1998). Over the years, there is an increasing number of higher educational institutions have embraced e-learning, however, with a lesser number of higher education providers in Malaysia particularly private education providers as well as colleges provides e-learning to their learners. Why is it so? There are still doubts and hesitation on the e-approach especially for young school leavers who undergo their studies full-time. There are various dimensions of e-readiness have yet to be explored such as learner readiness, management readiness, personnel readiness, content readiness, technical readiness, environmental readiness, cultural readiness and financial readiness. We wish to study on young learners’ readiness on elearning only for this paper. This study will be conducted in various public and private higher education providers whereby its respondents are young learners. The outcome of this study will be useful for education providers to draw and provide suitable learning pedagogy to their learners as well as potential learners in order to engage in an effective teaching and learning process to their learners.